On the firing line Olympic Shooting Sports Training Center - Manaois, Anthony N.
Olympic shooting gas a great potential as an avenue for Filipino athletes to show their competence and excellence. Despite lacking support from the government, some of the country's best shooters have been successful in shooting sports in the international scene. This study establishes the present conditions of the shooting sports in the Philippines as well as its potential to become a frontrunner in the country's future sports development programs. Like other sports, shooting is an opportunity for recreation, a tool for youth development and an instrumental component in the national development. The study proposes the need for a shooting center training and holding a local and international shooting competitions. High-level training will be conducted at the facility for the present national shooters and future pool of athletes that will represent the Philippines in international competitions.